Forking in open source software: a case of Mambo - Li, Tingyu (2008)
The open source software has take an more and more important role in the world. The aim of this research is going to examine the factors of forking and the process of conflict in open source software. It would be surveyed by the case study research strategy and qualitative analysis as the case of Mambo forking. The results suggest a framework to explain how Mambo forked. Conclusively, the research might give a new thought of the forking phenomenon of open source software.